Conservative accession toward treatment of plexiform ameloblastoma in an 11-year-old girl - Avantika Tuli; Shivangi Chandra; Mahima Sehgal; Amrinder Singh Tuli; Monika Varshney (Wolters Kluwer Medknow Publications, 2017)
Ameloblastoma is the common form of aggressive benign tumor of the jaws, but it is rare in childhood. The treatment of ameloblastoma is controversial. Surgical treatment of ameloblastoma in children follows the principles of the clinical and pathological aspects of the tumor and poses a special problem due to the incomplete growth of the jaws. With a unicystic ameloblastoma, the procedure of choice is a conservative approach. This paper describes the conservative treatment of a plexiform unicystic ameloblastoma in a child involving curettage of the tumor and the extraction of four teeth under general anesthesia, with a good prognosis of the case.